SEASONAL VARIATION IN THE STABLE CARBON AND NITROGEN ISOTOPE BIOGEOCHEMISTRY OF A COASTAL COLD OCEAN ENVIRONMENT - Ostrom N.E.; Macko S.A.; Deibel D.; Thompson R.J. (My University, 1997)
The carbon and nitrogen isotopic composition of seston, sinking POM, and inorganic nitrogen was determined on a seasonal basis in a coastal cold-ocean embayment, Conception Bay, Newfoundland. Isotopic variation in particulate organic matter and nitrate as a function of depth and season was large and reflected the dynamic nature of carbon and nitrogen cycling in continental shelf environments. Seston and sinking POM were most similar in δ13C and δ15N during a spring bloom in March and April when diatom productivity dominated both of these particle fractions. Following the spring bloom, differences in the isotopic composition of seston and sinking POM were related to distinctions in residence times or phytoplankton species contributing to these materials. Shifts in the δ15N and δ13C of sinking POM toward those of seston in late summer were indicative of an increase in zooplankton grazing and fecal pellet production. Evidence for the control of phytoplankton δ13C by pCO2 during the spring bloom was illustrated by a maximum in the δ13C of seston concomitant with reductions in the concentration of DIC and high chlorophyll fluorescence from March through mid-April. Following the spring bloom, seston δ13C values were decreased in association with increases in DIC concentration and a change in phytoplankton species composition.The δ15N of nitrate in Conception Bay averaged 0.2%%, a value that is markedly lower than those of other oceanic environments and most likely reflects isotopic discrimination associated with mineralization and nitrification in the cold, well oxygenated waters of this system. Seston was considerably more enriched in 15N than nitrate at all times, which clearly indicated that in contrast to other environments, an isotope effect during nutrient uptake was not the predominant control on the isotopic character of seston in this bay. The exact processes contributing to enrichments in 15N in seston are not clear, but most likely include regenerative processes such as losses of dissolved organic nitrogen and ammonium, microzooplankton grazing, protein hydrolysis, and microbial degradation. In addition, losses of 15N depleted material as sinking POM may have contributed to the high δ15N values for seston in Conception Bay. In that marked enrichments in the 15N content of seston were most pronounced at the base of the chlorophyll fluorescence maximum in spring, the magnitude of isotopic fractionation during these processes may be controlled by the availability of phytoplankton-produced substrates. Seston δ15N also increased at the end of the spring bloom and may therefore reflect a change in the nutrient source supporting productivity from nitrate, with a low δ15N, to regenerated nitrogen. In this manner, the δ15N of seston may be a sensitive indicator of the transition from productivity based on nitrate to one based on regenerated ammonium. The large distinction in δ15N between seston and nitrate in Conception Bay may be related to a greater supply of nitrate via destratification and coastal upwelling, which initiates primary production and regenerative processes, than is typical of more oligotrophic environments.